Evaluation of a pcv2 vaccine on finishing pig growth performance and mortality rate - Jacela, J.Y.; Tokach, Michael D.; DeRouchey, Joel M.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 2,553 pigs (PIC L337 × C22) were used in two experiments in a commercial research barn to evaluate the effects of a commercially available Porcine Circovirus Type 2 (PCV2) vaccine on finisher pig growth rate, feed efficiency, and mortality rate. Pigs in Exp. 1 were vaccinated at 9 and 11 wk of age while pigs in Exp. 2 were vaccinated earlier at 5 and 7 wk of age. In Exp. 1, 1,300 pigs were individually weighed and the vaccine treatment administered 15 and 1 d before being placed on test in the finisher. In Exp. 2 1,253 pigs were used and randomly allotted based on nursery pen average pig weight and the vaccine treatment administered 41 and 27 d before being placed on test in the finisher. Pen weights were obtained on d 0 and every 2 weeks until the end of the trial. Feed intake was recorded on a pen basis. In Exp 1, growth rate, feed intake, feed efficiency, and mortality were improved (P<0.05) in vaccinated pigs compared to unvaccinated pigs. In Exp. 2, there was a vaccine by sex interaction (P<0.01) for ADG 2. The interaction was the result of the vaccine increasing ADG to a greater extent in barrows than in gilts. The interaction for ADG resulted in a vaccine by sex interaction for market weight (P<0.05). Vaccinated barrows were 10.6 lb heavier compared to unvaccinated control barrows while vaccinated gilts were only 2.1 lb heavier than unvaccinated gilts at market. In Exp. 2, ADFI and F/G were numerically better and mortality rate was decreased for vaccinated pigs compared to control pigs. In both experiments, mortality rates were lower (P<0.05) in vaccinated pigs. Vaccinated pigs had 2.6 and 5.9% less mortality than nonvaccinated pigs in Exp. 1 and 2, respectively. The commercial PCV2 vaccine used in this study was effective at reducing mortality and increasing growth rate in finisher pigs with histopathologic lesions suggestive of Porcine Circoviral Disease (PCVD).
Keywords: Swine; Health; PCVD; PCV2